Pembangunan Digitalisasi Bumdes Desa Mekarmulya Kecamatan Teluk Jambe Barat Kabupaten Karawang - Dimas Al Aziz Celsa; Lukmanul Hakim; Kariena Febriantin (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine whether the management of funds carried out at BUMDes in Mekarmulya Village, Telukjambe Barat District, Karawang Regency was still not sufficient to increase satisfaction with meeting the needs of the Mekarmulya community in particular. So the researchers used the type or qualitative research method at the Mekarmulya Village Office. Qualitative research can be interpreted as a series of activities or processes to collect data or information that is reasonable about a problem in terms of aspects, or fields of object, digitization according to the Minister of Villages, Development of Disadvantaged Regions and Transmigration (Mendes PDTT) Abdul Halim Iskandar said, digitalization the village economy is one of the main programs in village development efforts, therefore seeing the rapid development of technology, the BUMDes of Mekarmulya Village, Telukjambe Barat District, Karawang Regency must carry out digitalization development in trade using digital markets that are already circulating.